Population and Health in Developing Countries - Gaimard, Maryse. author. aut Link
XIX, 165 p.
Keywords: This book provides an overview of the health of developing nations in the early twenty-first century. The basic assumption is that the health of a population is not independent of broader demographic trends, and does follow the health transition model. The coverage is broad, ranging from health transition in developing countries, to the health of women, to an analysis of morbidity. Population health is an essential component of human and social development. As both a means and an end of development, health lies at the heart of underdevelopment, and ranks first on the list of international priorities. The WHO slogan ‘Health for all in 2000’ reflects the spirit of a more general movement in favor of health promotion throughout the world. But the developing world is far from reaching this aim. The health of populations has improved in developing regions but there are still deep inequalities, and serious problems remain, especially in Sub-Saharan Africa. After reviewing the core concepts of population health, the book examines health transition in developing countries, a process that has resulted in a double burden of diseases. A discussion of mortality in developing countries serves to highlight the high rates of child mortality in these regions. The book devotes a full chapter to women’s health, and its chapter-length analysis of morbidity highlights the double burden weighing down developing populations and concludes with an analysis of health systems in developing countries.